A formal GSPN model of a virtual doctor dialogue system. (May 2023) - Bourbakis, Nikolaos; Mallios, Stavros
This paper presents a formal generalized stochastic Petri net (GSPN)–based modeling of a virtual doctor (VDr) dialogue system. The interaction model between the VDr dialogue system and the human patient is a modified version of the Wickens model. The purpose of this model is to provide a better understanding of the interaction between the VDr dialogue system and the patient, as well as the integration of other components in the system, such as the patient's medical history and emotions. Initially, the formal definition of the GSPN model of the VDr dialogue system is presented by incorporating the token color concept, which is a feature of Color GSPNs. Then, the GSPN formal modeling is described. Note that, the GSPN model presented here is at the simulation level and not a product. Furthermore, some examples are provided with the intention of facilitating the understanding of the token color utilization and the different GSPN markings.